Advances in Delivery Mechanisms of CRISPR Gene-Editing Reagents in Plants - Laforest, Larissa C.; Nadakuduti, Satya Swathi (Frontiers in Genome Editing, 2022)
Gene-editing by CRISPR/Cas systems has revolutionized plant biology by serving as a functional genomics tool. It has tremendously advanced plant breeding and crop improvement by accelerating the development of improved cultivars, creating genetic variability, and aiding in domestication of wild and orphan crops. Gene-editing is a rapidly evolving field. Several advancements include development of different Cas effectors with increased target range, efficacy, and enhanced capacity for precise DNA modifications with base editing and prime editing. The existing toolbox of various CRISPR reagents facilitate gene knockouts, targeted gene insertions, precise base substitutions, and multiplexing. However, the major challenge in plant genome-editing remains the efficient delivery of these reagents into plant cells. Plants have larger and more complex genome structures compared to other living systems due to the common occurrence of polyploidy and other genome re-arrangements. Further, rigid cell walls surrounding plant cells deter the entry of any foreign biomolecules. Unfortunately, genetic transformation to deliver gene-editing reagents has been established only in a limited number of plant species. Recently, there has been significant progress in CRISPR reagents delivery in plants. This review focuses on exploring these delivery mechanisms categorized into Agrobacterium-mediated delivery and breakthroughs, particle bombardment-based delivery of biomolecules and recent improvements, and protoplasts, a versatile system for gene-editing and regeneration in plants. The ultimate goal in plant gene-editing is to establish highly efficient and genotype-independent reagent delivery mechanisms for editing multiple targets simultaneously and achieve DNA-free gene-edited plants at scale.